Cognitive Processing Of Da'wah Messages On Tiktok: A Qualitative Study Of Islamic Communication and Broadcasting Students At The State Islamic University Of North Sumatra - Tio Gibran; Khatibah; Ikhwan Kurnia Hutasuhut (Jurnal Ilmu Sosial dan Humaniora, 2026)
The widespread exposure to short-form and fast-paced TikTok content has the potential to influence the cognitive processing of da'wah messages when audiences lack adequate cognitive capacity to process the information. This study aims to describe the cognitive understanding process of students from the Islamic Broadcasting and Communication (KPI) Program at Universitas Islam Negeri Sumatera Utara regarding the da'wah messages delivered by Risyad Bayasud on TikTok. This study employed a qualitative approach using the The widespread exposure to short-form and fast-paced TikTok content has the potential to influence the cognitive processing of da'wah messages when audiences lack adequate cognitive capacity to process the information. This study aims to describe the cognitive understanding process of students from the Islamic Broadcasting and Communication (KPI) Program at Universitas Islam Negeri Sumatera Utara regarding the da'wah messages delivered by Risyad Bayasud on TikTok. This study employed a qualitative approach using the Qualitative Content Analysis method. The participants consisted of active KPI students selected through purposive sampling based on their experience accessing and consuming Islamic preaching content on TikTok. Five of Risyad Bayasud's da'wah videos were purposively selected according to their thematic relevance to the research focus and were used as stimuli prior to the in-depth interviews. Data were collected through observation, in-depth interviews, and documentation. The data analysis involved determining the unit of analysis, identifying meaning units, coding, categorizing, developing themes, and interpreting the findings using Robert M. Gagné's Information Processing Theory. The findings reveal that the cognitive understanding process occurs through three sequential stages: selective attention, meaning interpretation within short-term memory, and knowledge internalization into long-term memory. Participants' attention was primarily attracted by the shock effect and the relevance of the presented topics, while the interpretation process was strengthened by the preacher's communicative, empathetic, and contextual delivery style, which encouraged spiritual reflection. Subsequently, the interpreted messages were internalized into new religious knowledge that fostered greater self-awareness and motivation for self-improvement. The study also found that cognitive overload, resulting from rapid scrolling habits, along with the limited opportunity for tabayyun (verification or clarification) due to one-way communication, constituted the primary barriers to the internalization of da'wah messages in short-video media. These findings suggest that the effectiveness of digital da'wah depends not only on the quality of its message but also on the audience's cognitive process of attending to, interpreting, and internalizing religious information. based on their experience accessing and consuming Islamic preaching content on TikTok. Five of Risyad Bayasud's da'wah videos were purposively selected according to their thematic relevance to the research focus and were used as stimuli prior to the in-depth interviews. Data were collected through observation, in-depth interviews, and documentation. The data analysis involved determining the unit of analysis, identifying meaning units, coding, categorizing, developing themes, and interpreting the findings using Robert M. Gagné's Information Processing Theory. The findings reveal that the cognitive understanding process occurs through three sequential stages: selective attention, meaning interpretation within short-term memory, and knowledge internalization into long-term memory. Participants' attention was primarily attracted by the shock effect and the relevance of the presented topics, while the interpretation process was strengthened by the preacher's communicative, empathetic, and contextual delivery style, which encouraged spiritual reflection. Subsequently, the interpreted messages were internalized into new religious knowledge that fostered greater self-awareness and motivation for self-improvement. The study also found that cognitive overload, resulting from rapid scrolling habits, along with the limited opportunity for tabayyun (verification or clarification) due to one-way communication, constituted the primary barriers to the internalization of da'wah messages in short-video media. These findings suggest that the effectiveness of digital da'wah depends not only on the quality of its message but also on the audience's cognitive process of attending to, interpreting, and internalizing religious information.